Medical Graduate’s Choice of Dentistry (Medical Forum Monthly, 2024)
Objective: To determine the factors affecting how medical graduates of Karachi choose their dental health care providers.Study Design: Observational / descriptive / cross sectional study.Place and Duration of Study: This study was carried out at Jinnah Medical and Dental College, Karachi from August 2014 to December 2014.Materials and Methods: The study was conducted at Jinnah Medical and Dental College. A 11-item questionnaire was used to collect the data. The data was collected from medical college graduates of Karachi to determine the factors affecting how medical graduates choose their dental health care providers. The questionnaire involved attributes ranging from dental practice to reputation, X-ray facility within clinics, skills/ experience, timings and availability, sterilization, location, Clinical Setup (general appearance/ambiance), qualification, Payment Plans (installments, credit cards, etc.) and Treatment charges. The study included 382 doctors. The data was stored in excel worksheet and was analyzed using SPSS.Results: 26% of the respondents selected ‘skills/ experience’ as the most important attribute in selecting a dentist while 20% of the respondents picked ‘sterilization’ and 17% of the respondents chose ‘qualification’ as their top reason for the selection of dentist. Reputation of the dentist was selected by 14% of the respondents whereas 10 % selected treatment charges as their reason for selecting a dentist. Clinical setup and location accounted for 9 and 4 % respectively.Conclusion: In conclusion skills/ experience, reputation of the dentist and sterilization standards of clinic are were the most important factors while selecting a dentist.